Robots and AI: A New Economic Era - Lili Yan Ing; Gene M. Grossman (Routledge, 2023)
Robots and artificial intelligence (AI) are powerful forces that will likely have large impacts on the size, direction, and composition of international trade flows. This book discusses how industrial robots, automation, and AI affect international growth, trade, productivity, employment, wages, and welfare. The book explains new approaches on how robots and artificial intelligence affect the world economy by presenting detailed theoretical framework and country-specific as well as firm-product level-specific exercises. This book will be a useful reference for those researching on robots, automation, AI and their economic impacts on trade, industry, and employment.
Keywords: 330; Artificial Intelligence; Economic Growth; Firm Level Study; Industrial Robots; Industry; International Trade; Labour; Political Economy; Welfare